KEARIFAN LOKAL PETANI LERENG GUNUNG LAWU DALAM MENGANTISIPASI BANJIR DAN TANAH LONGSOR (Studi Kasus Di Desa Wonorejo Kecamatan Jatiyoso Kabupaten Karanganyar) - Agung Wibowo (Universitas Sebelas Maret, 2007)
This research conducted at the village of Wonorejo, Sub-District of Jatiyoso, Regency of Karanganyar with consideration that the region is proven shalom be happened flood an landside though is seen from the topography of that area included sensitive of flood and landslide. This research type is qualitative with using th e strategy of mono case study and fenomenologies approach. Used analysis technique is mono case analysis, in the each case process the analysis will be conducted by using the interactive analysis model (reduction data, presented data and verification.).Cultural values friction is progressively felt, farm allotment, more considering only the economic value them paying attention to environmental aspect, and experienced resource conservation. making of house Location, what is not based again for local wisdom, at local society. In conducting the effort peasant, orienting at commodity which quickly yield and high economic valuable without considering ecological balance. Existence of local culturol value friction seed ·what mirror in local wisdom, if it is not made balance to with the policy, or regulation mounted local felt concerned about will affect, at eroding of local wisdoms of peasant, which during the time still hold out, in managing effort peasant and also anticipate the floods and landslide.